RATING OF THE REGIONS OF UKRAINE BY THE LEVEL OF COMPETITIVE ADVANTAGES OF INDUSTRY - S.О. Ishchuk (Економіка та право, 2018)
The magnitude and heterogeneity of the industrial sector of the national economy requires its in-depth research in a regional dimension. The urgency of this problem is due to increased competition in world markets and the spread of globalization processes. The purpose of the article is to evaluate the activity and efficiency of the functioning of the industrial sector of the economy of the regions of Ukraine and build the rating of the latter on the level of competitive advantages of the industry. Using the author’s methodical approach, integral indices of competitive advantages characterizing activity (production, export, investment, capital, innovation) and efficiency (resource and economic) of Ukraine are calculated. According to the results of the calculation, the grouping of regions by the level of efficiency and activity of the functioning of the industrial sector of the economy has been carried out. The indices of competitive advantages are reduced to the general integral index, based on which values the regional ranking is based on the level of competitiveness of the industry. The key trends of development of domestic industrial production in the regional section are determined. It was determined that in 2016 the growth of values of such indicators was achieved in the most regions of Ukraine: the share of industrial production in the volume of sales of products (goods and services), the growth rates of capital investments in industry, growth rates of non-current assets, return on assets, labor productivity, profitability of operating activities, as well as indicators of innovation activity. At the same time, there was a decrease in the growth rate of the volume of industrial products sold, the share of non-current assets in assets, the share of industry in the total volume of direct foreign investments and the growth rates of the latter, as well as indicators of export activity. In general, the results of the integrated assessment of the competitive advantages of the industry in the regions of Ukraine provide an opportunity to create an objective analytical basis for making informed managerial decisions regarding the formation of a strategy for the development of the industrial sector of the national economy, in particular at the regional level.